Space-use strategy affects energy requirements in Barents Sea polar bears - Blanchet, Marie-Anne; Aars, Jon; Andersen, Magnus; Routti, Heli (Marine Ecology Progress Series, 2020)
Polar bears Ursus maritimus are currently facing rapid environmental changes with loss of sea ice and shifts in their prey distribution. Two distinct ecotypes exist in the Barents Sea, where sea ice is decreasing at the highest rate in the Arctic. Coastal bears remain within the Archipelago of Svalbard year-round, whereas offshore bears follow the marginal ice zone (MIZ). We explored these 2 ecotypes’ habitat use, activity and energy needs as well as seasonal variation within these parameters. During the period from 2011-2018, adult female polar bears were equipped with GPS collars and activity sensors (n = 84); 46 of these were equipped with conductivity switches to record aquatic behaviour. Offshore bears travelled longer distances at a higher speed on land and at sea away from land and had a higher activity rate compared to coastal bears. This translated into higher overall energy expenditure. Offshore bears also undertook more distant and energetically costly trips from land to the MIZ, swimming in open water. Both ecotypes showed similar seasonal patterns of activity and movement consistent with their life history linked to sea ice phenology. Despite higher energy expenditure, the offshore strategy seemed to be as profitable as the coastal one as females had marginally better spring body condition, likely due to their specialized high caloric diet of seals throughout the year. However, both ecotypes are currently experiencing habitat changes. Future studies should aim to predict how rapidly declining sea ice in the Barents Sea may challenge polar bears energetically during the coming decades.